Analysis of The Role of The Independent Auditor on Reducing Time Lags in Financial Reporting and Earnings Management - Kiryanto Kiryanto; Lisa Kartikasari; Anggi Gita Cahyani; Agus Triyani (Jurnal Akuntansi Indonesia, 2023)
ABSTRACT This study aims to analyze differences in the timeliness of financial reporting and earnings management in terms of auditor quality in manufacturing companies on the Indonesia Stock Exchange. based on the purposive sampling technique, a sample of 37 companies was obtained so that for 3 years of observation the data processed were 111. The hypothesis was tested using the Independent Samples Test different test. The results showed that there was no difference in the level of audit delay between companies audited by big four auditors or not. Meanwhile, the level of corporate earnings management audited by the big four or not the big four shows different results. This shows that the role of independent auditors in reducing earnings management is successful. Keywords: Auditor Quality, Audit Delay and Earnings Management